MEMBANGUN APLIKASI MUTLIMEDIA PLAYER MENGGUNAKAN JAVA MEDIA FRAME WORK - Wahyu Widarti, Dinny; Noor, Muhammad (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2012)
Java Media Framework is a multimedia application program used to enter data audio and video media into a java application player. This multimedia application serves as an audio player and video player. With a java-based multimedia applications, computer users can easily play and use these applications with multi-operating system, not just the windows operating system, but also support other operating systems such as rheumatic pain. Therefore, computer users have no difficulty in running multimedia applications based on the java media framework. Multimedia player application makes it easy for the users computer as a media player audio and video applications as well as useful in the IT world for the java programmers to manipulate within the range of multimedia applications. From the results obtained that the player java application makes it easy for Java programmers to be able to develop a java program framework. Keywords: Applications Multimedia Player, Java Media Framework